The Role of The Fisheries Court in The Settlement f Illegal Fishing Disputes in Indonesia - Wiharja, Mahegi Ashardani Warna Adhi; M.S, Edith Ratna (Fakultas Syariah INSURI Ponorogo, 2024)
The practice of illegal fishing or fish theft in Indonesian waters is still ongoing until now. These problems result in many parties being harmed, so it is very necessary to enforce the law that regulates these acts. The purpose of this study is to analyze the position of the fisheries court as a special court and how the fisheries court solves illegal fishing problems related to fishing without being equipped with documents or permits. This research is a qualitative research whose implications are descriptive analytical. In connection with this approach, the type of normative juridical approach used is the legal approach. The result of this study is that the fisheries court in its position has the authority to examine, adjudicate, and decide on criminal acts in the fisheries sector as a special court within the general judicial environment. As for why the fisheries court is a special court because the judges are not pure, there are judges who are in control of the fisheries sector. As well as the existence of foreign vessels that commit fish theft without being equipped with documents or permits, they will be given sanctions and criminal penalties in accordance with Law Number 45 of 2009 which was previously revised from Law Number 31 of 2004. The punishment given to illegal fishing perpetrators can be in the form of imprisonment, fines, and revocation of rights. Illegal fishing perpetrators must receive rewards by being subject to large fines for committing violations.